Between panic and hope: Indigenous peoples, gold, violence(s) and FPIC in Colombia, through the lens of time. Issue 1 (2nd January 2019) - Weitzner, Viviane
Abstract: This article considers the relationship between gold mining, violence(s) and Indigenous peoples through the lens of legal pluralities with a focus on the dimension of time. Drawing on the specific case of the Embera Chamí of the Resguardo Indígena [Indigenous Reserve] of Cañamomo Lomaprieta in Colombia, I ask: What can an analysis through the lens of time unearth around the type of violence(s) that extractives engender for Indigenous peoples and their ancestral lands? I ground my analysis with concepts emerging from the literature around extractives and legal pluralities, such as Stuart Kirsch's (2014 ) "politics of time'; Boaventura Santos' (2002) "instant" and "glacial time"; and the "lethal" and "ancestral time" that emerge from my own work with Indigenous and Afro-Descendant peoples in Colombia. I develop a typology of actors and legalities vying to regulate the Resguardo's gold, further developing my concept of "raw law" through the dimension of time. And I show what happens when the Resguardo's authorities appropriate free, prior and informed consent as a tool towards self-government within this context of inter-i-legality. I take up Lemaitre and Sandvik's (2015) call to theorize differently contexts of violence, reflecting also critically on ethical implications for activism and collaborative research.